ADAPTASI KELUARGA DALAM PROSES PEMBELAJARAN ONLINE PADA MASA PANDEMIK COVID-19 DI KOTA PEKANBARU - Safitri, Armi Liana Eka; Marnelly, T. Romi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research aims to determine the Adaptation Of Families In The Online Learning Process During The Covid-19 Pandemic In Pekanbaru City, throughthe parents of students at SD Negeri 111 Pekanbaru City. Family adaptation in the online learning process is seen from the provision of facilities and infrastructure, time, economy and the obstacles that exist during online learning to parents. To get the results of the study, the researcher used a descriptive quantitative research method with a total of 63 parents. The results of this study indicate that the majority of family adaptation in the online learning process during the Covid-19 pandemic in Pekanbaru City and economic barriers, parents ‘knowlegde and activities do not really affect it. Adaptation of parents is high so that obstacles do not really affect the process of adaptation online learning that is dones at home. Parents have being a substitute for teachers, parents must take the time to accompany, supervise, and motivate children.   Keywords: Adaptation, Family, Online Learning